Potencial antitumoral do óleo essencial das folhas de Croton grewioides Baill. (Euphorbiaceae): um estudo in vitro - Andrade, Camyla Caroliny Neves de (2021)
The term cancer is a set of diseases that present uncontrolled cell growth and differentiation, as well as invasive and metastatic capacity. Despite advances in cancer therapy, characteristics such as high cytotoxicity and development of resistance to treatment still limit its effectiveness. The plant species Croton grewioides Baill. (Euphorbiaceae), popularly known as “canelinha”, “smell caatinga” or “smell canelinha”, is a species from the Brazilian semiarid region with antidiarrheal, antioxidant and antitumor activity in a mouse sarcoma 180 model. In this perspective, the aim of the present work was to evaluate the antitumor potential of the essential oil extracted from the leaves of C. grewioides (OEC), through in vitro assays. Cytotoxicity was evaluated in human tumor (HCT-116, HeLa, MCF-7, PC-3, MDA-MB-231, SKMEL-28) and non-tumor (HaCaT) cell lines through the reduction assay of MTT (3-(4,5- dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide). OEC induced greater cytotoxicity in melanoma strain, SK-MEL-28, obtaining an inhibitory concentration 50% (IC50) of 70.0 μg/mL, in 72 hours. In vitro cytotoxicity was evaluated in a non-tumor strain, HaCaT, obtaining an IC50 value of 214.0 μg/mL, after 72 hours. The standard drug, doxorubicin (DOX), showed high toxicity in SK-MEL-28 and in HaCaT, with IC50 values of 4.0 and 0.28 μM, respectively. To elucidate the in vitro mechanisms of action involved in the antitumor activity of OEC, its effects on the cell cycle, induction of apoptosis and production of reactive oxygen species (ROS) were evaluated using concentrations corresponding to IC50 and double (70, 0 and 140.0 µg/ml) in SK-MEL28 cells. After 48 hours of treatment, OEC altered the progression of the cell cycle, inducing an increase in the percentage of cells in the G2/M phase (p<0.01) and the appearance of the sub-G1 fraction (p<0.0001), which is indicative of apoptosis. Through confocal microscopy analysis, morphological characteristics indicative of cell death by apoptosis were observed, such as formation of blebs in the membrane, apoptotic bodies and chromatin condensation, which were confirmed by the externalization of phosphatidylserine through annexin V-FITC labeling (p<0.0001) after 48 hours of treatment with OEC. Regarding the production of ROS, OEC significantly reduced the level of ROS (p<0.0001), at both concentrations tested after 24 hours of treatment, suggesting that the antitumor effect of OEC is associated with an antioxidant action. In conclusion, the results presented indicate that OEC has in vitro antitumor activity in cells of the melanoma lineage, SK-MEL-28, by promoting changes in the cell cycle, induction of apoptosis and antioxidant effect, in addition to presenting low toxicity in the melanoma lineage. non-tumor cells (HaCaT).